Concept of fast dissolving formulations for use in acute treatment conditions â€“ introspection, thoughts and perspectives - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
In a recent issue of AJP, Ranagasamy et al. (2009) have provided a succulent report on the development of a fast dissolving tablet of terbutaline sulfate for possible human use in the timely management of asthmatic episodes.[1] The design and evaluation part of the work suggested that careful consideration was taken from the selection of excipients until the dissolution testing of the tablets to confirm its intended utility.[1] However, an important missing link in this work was to confirm whether or not such a system would work under in vivo conditions to ensure rapid drug delivery has not been compromised. Hence, it need to be questioned and challenged when emphatic conclusion stating that â€œthe new fast dissolving terbutaline formulation is better than the conventional tablet dosage form used in the management of asthmaâ€ has been made in the published work without adequate support to back it up.[1] While it is acknowledged that it may be difficult for academic/research institutions or fledgling biotechs to perform in vivo evaluations due to the lack of resources, trained personnel and/or funding issues, in some extraordinary cases it may be a good idea to explore testing of the new formulation in a preclinical model for getting clarity on the in vivo performance of the new formulation. Needless to say, the final utility of the innovation and design of the new formulation is solely dependent on its in vivo performance.